2016
DOI: 10.1002/ijc.30124
|View full text |Cite
|
Sign up to set email alerts
|

Early sorafenib‐related adverse events predict therapy response of TACE plus sorafenib: A multicenter clinical study of 606 HCC patients

Abstract: The purpose of our study was to test the hypothesis that sorafenib-related dermatologic adverse events (AEs) as an early biomarker can predict the long-term outcomes following the combination therapy of transarterial chemoembolization (TACE) plus sorafenib (TACE-S). The intermediate-stage hepatocellular carcinoma patients who received either TACE-S or TACE-alone treatment were consecutively included into analysis. In the TACE-S group, patients with grade 2 dermatologic AEs within the first month of sorafenib i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
(88 reference statements)
2
16
0
Order By: Relevance
“…Because of the lack of reliable biomarkers for sorafenib use, dermatologic AEs related to sorafenib have become widely recognized as surrogate markers for efficacy in patients with HCC . The prognostic value of these dermatologic AEs was also confirmed in our very recent multicentre clinical study of 606 HCC patients, which demonstrated that sorafenib‐related dermatologic AEs may be used as clinical indicators to identify responders to sorafenib and those who are more likely to benefit from TACE‐S treatment . Indeed, patients who develop dermatologic AEs might constitute the ideal population in whom the addition of sorafenib would work.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Because of the lack of reliable biomarkers for sorafenib use, dermatologic AEs related to sorafenib have become widely recognized as surrogate markers for efficacy in patients with HCC . The prognostic value of these dermatologic AEs was also confirmed in our very recent multicentre clinical study of 606 HCC patients, which demonstrated that sorafenib‐related dermatologic AEs may be used as clinical indicators to identify responders to sorafenib and those who are more likely to benefit from TACE‐S treatment . Indeed, patients who develop dermatologic AEs might constitute the ideal population in whom the addition of sorafenib would work.…”
Section: Discussionmentioning
confidence: 88%
“…AEs were evaluated every 2 weeks by two independent physicians (W. Bai and G. Han). Consistent with previous studies, grade 2 was selected as the cut‐off . We defined patients with skin toxicity ≥ Grade 2 as dermatologic responders and patients with skin toxicity < Grade 2 as dermatologic nonresponders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…beyond the Milan criteria), TACE barely accomplished a 3-year survival rate of 30% even in experienced centers [9,10]. The use of TACE with External Beam Radiotherapy [16] or Sorafenib [17,18] also failed to demonstrate a satisfactory patient survival. Suboptimal survival (3-year survival of ~20%) has also been reported with Yttrium-90 selective internal radiation therapy in patients with intermediate-stage HCC deemed unsuitable for LT [19][20][21].…”
Section: Discussionmentioning
confidence: 99%